HIF-1α Stabilization Increases miR-210 Eliciting First Trimester Extravillous Trophoblast Mitochondrial Dysfunction - Anton, Lauren; DeVine, Ann; Polyak, Erzsebet; Olarerin-George, Anthony; Brown, Amy G.; Falk, Marni J.; Elovitz, Michal A. (Frontiers in Physiology, 2019)
Preeclampsia is associated with first trimester placental dysfunction. miR-210, a small non-coding RNA, is increased in the preeclamptic placenta. The effects of elevated miR-210 on placental function remain unclear. The objectives of this study were to identify targets of miR-210 in first trimester primary extravillous trophoblasts (EVTs) and to investigate functional pathways altered by elevated placental miR-210 during early pregnancy. EVTs isolated from first trimester placentas were exposed to cobalt chloride (CoCl2), a HIF-1α stabilizer and hypoxia mimetic, and miR-210 expression by qPCR, HIF1α protein levels by western blot and cell invasion were assessed. A custom TruSeq RNA array, including all known/predicted miR-210 targets, was run using miR-210 and miR-negative control transfected EVTs. Mitochondrial function was assessed by high resolution respirometry in transfected EVTs. EVTs exposed to CoCl2 showed a dose and time-dependent increase in miR-210 and HIF1α and reductions in cell invasion. The TruSeq array identified 49 altered genes in miR-210 transfected EVTs with 27 genes repressed and 22 enhanced. Three of the top six significantly repressed genes, NDUFA4, SDHD, and ISCU, are associated with mitochondrial function. miR-210 transfected EVTs had decreased maximal, complex II and complex I+II mitochondrial respiration. This study suggests that miR-210 alters first trimester trophoblast function. miR-210 overexpression alters EVT mitochondrial function in early pregnancy. Mitochondrial dysfunction may lead to increased reactive oxygen species, trophoblast cell damage and likely contributes to the pathogenesis of preeclampsia.